Truthful nudging - Cohen, Shlomo (Journal of medical ethics, 2018)
Zealous nudging can deteriorate into paternalistic bullshitting (in Harry Frankfurt’s technical sense). To the extent that William Simkulet’s paper is a reminder against that danger, it does us good service.1 Simkulet, however, makes the far bolder claims that nudging just is bullshitting and that—since bullshitting deviates from truthfulness, and truthful disclosure is essential for valid consent—nudging invalidates informed consent. These bolder claims involve a set of errors.The problem starts with Simkulet’s formal definition of ‘bullshit’, which says that conveying x while intending one’s audience to believe y is sufficient for bullshit. This, however, is not true since the bullshitter’s not caring whether x is true is constitutive of bullshitting, and hence a necessary condition. Why, we then ask, must such lack of care be the case with the doctor who nudges? It is at least prima facie easy and intuitive to think of scenarios in which the ethical doctor is staunchly committed to telling the truth while simultaneously acting on additional motives regarding the expected effects of what is said. If the doctor cares about saying only truths (as of course he should), he is not a bullshitter.Having communicative motivations that transcend the trivial motive of transmitting the truth of the literal content of what is said is normal and indeed normative in conversations of regular (non-autistic) people.2 …